Graphene and Other 2D Colloids: Liquid Crystals and Macroscopic Fibers. Issue 14 (24th February 2017) - Liu, Yingjun; Xu, Zhen; Gao, Weiwei; Cheng, Zhengdong; Gao, Chao
Abstract : Two‐dimensional colloidal nanomaterials are running into renaissance after the enlightening researches of graphene. Macroscopic one‐dimensional fiber is an optimal ordered structural form to express the in‐plane merits of 2D nanomaterials, and the formation of liquid crystals (LCs) allows the creation of continuous fibers. In the correlated system from LCs to fibers, understanding their macroscopic organizing behavior and transforming them into new solid fibers is greatly significant for applications. Herein, we retrospect the history of 2D colloids and discuss about the concept of 2D nanomaterial fibers in the context of LCs, elaborating the motivation, principle and possible strategies of fabrication. Then we highlight the creation, development and typical applications of graphene fibers. Additionally, the latest advances of other 2D nanomaterial fibers are also summarized. Finally, conclusions, challenges and perspectives are provided to show great expectations of better and more fibrous materials of 2D nanomaterials. This review gives a comprehensive retrospect of the past century‐long effort about the whole development of 2D colloids, and plots a clear roadmap — "lamellar solid — LCs — macroscopic fibers — flexible devices", which will certainly open a new era of structural‐multifunctional application for the conventional 2D colloids. Abstract : 2D colloidal nanomaterials are experiencing a full‐scale renaissance after the enlightening research of graphene. The history of 2D colloidal liquid crystals is comprehensively reviewed from the first V2 O5 colloid to the recently discovered graphene (oxide) and other graphenelike 2D nanomaterials. Their attractive solution‐processible properties facilitate the construction of macroscopic fibers with versatile functionalities.